2018
DOI: 10.1371/journal.pone.0187663
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of hemoglobin measurement tools and their accuracy and reliability when screening for child anemia in Rwanda: A randomized study

Abstract: Blood hemoglobin (Hb) is a common indicator for diagnosing anemia and is often determined through laboratory analysis of venous samples. One alternative to laboratory-based methods is the handheld HemoCue® Hb 201+ device, which requires a finger prick and wicking of blood into a pretreated cuvette for analysis. An alternative HemoCue® gravity method is being investigated for improved accuracy. Further, recent developments in noninvasive technologies could provide an accurate, rapid, safe, point-of-care option … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 15 publications
3
72
0
2
Order By: Relevance
“…One study in 2018 on child anemia in Rwanda found a sensitivity of 89% and a specificity of 86%. 21 Lower and upper limits of agreement for both the Pronto-7 (Ϫ3.29 and 2.25, respectively) and the HemoCue 201ϩ (Ϫ3.57, 1.61, respectively) were too wide to recommend either device as a full replacement for a blood test because a potential difference of 2-3 g/dL in either direction is significant. However, the demonstrated sensitivity and specificity of either device, combined with their ease of use, means that these devices can potentially be utilized to screen for anemia in patients in the ED setting.…”
Section: Discussionmentioning
confidence: 99%
“…One study in 2018 on child anemia in Rwanda found a sensitivity of 89% and a specificity of 86%. 21 Lower and upper limits of agreement for both the Pronto-7 (Ϫ3.29 and 2.25, respectively) and the HemoCue 201ϩ (Ϫ3.57, 1.61, respectively) were too wide to recommend either device as a full replacement for a blood test because a potential difference of 2-3 g/dL in either direction is significant. However, the demonstrated sensitivity and specificity of either device, combined with their ease of use, means that these devices can potentially be utilized to screen for anemia in patients in the ED setting.…”
Section: Discussionmentioning
confidence: 99%
“…Sensors are available for different‐sized fingers. However, the reading may be influenced by skin color …”
Section: Anemia Assessmentmentioning
confidence: 99%
“…Therefore, there is an intense need for measuring TCAL to evaluate the efficacy of chemotherapy. Chemotherapy of cancer patients also results in lowering of Hb level (Parker et al, 2018) which causes improper drug delivery to tumor cells. If the concentration of chemotherapy is decreased at the cellular level, then the tumorous cells' proliferation becomes more aggressive.…”
Section: Research Articlementioning
confidence: 99%